Crossbreeding beef cattle in western Uganda. 1. Performance of Ankole, Boran and zebu cows - Trail, J.C.M.; Sacker, G.D.; Fisher, I.L. (Cambridge University Press, 1971)
Three dam breeds, the indigenous Ankole and zebu, and the Boran from Kenya were mated to Boran Angus and Red Poll sires to investigate the relationship between dam body weight and progeny performance. Under artificial insemination, at least 10% fewer cows were detected on heat than under natural services, and 15% fewer artificially inseminated cows actually produced calves than did naturally served cows. The introduced Boran females were not inferior in calving percentage to the indigenous Ankole and zebu.The introduced Boran breeding cows were able to maintain their body weight at least as well as the indigenous Ankole and zebu cows. While cows which calved regularly and reared their calves could not maintain body weight, it was found that heavier cows conceived at a higher rate than lighter cows, cows heavier at parturition weaned heavier calves than lighter cows, and cows that reared heavier calves lost more, or gained less, body weight than cows that reared lighter calves. The reduction of lactation stress on cows by such methods as earlier weaning of calves, mating at the most suitable time of year, and possible nutritional supplementation at a stage in the cycle were recommended.